(untitled) (Research, Society and Development, 2021)
Today’s society needs to create global development mechanisms based on respect for nature, for universal human rights, for more economic justice. Sustainability is seen from the point of view of conformity between humanity and nature, relating the impact of economic activities on the environment. To think of sustainability is to think of a more equitable and egalitarian society. In this way the search for development goes through the aspect of human dignity, in that which is essential to man, food, from the right to healthier food choices, as well as more dignified lifestyles. Thus, this article sought to understand the various dimensions of the concept of development, based on Food and Nutrition Security, considering that despite Brazil being one of the world’s largest food producers, access to healthy food is not always a reality. To this end, data from bibliographic sources were used, such as scientific articles, discussions about the theme, data from research agencies such as IBGE, FAO, and DIEESE, among others. In this way it can be seen that one of the barriers to accessing food, especially healthy food, is the economic factor, as many families do not have a minimum income, due to factors such as unemployment or inflation.